Legal and Accounting Review of Sharia Fintech Financial Reports on Official Websites - Rifqiawan, Raden Arfan; Ghofur, Abdul; Murtadho, Ali; Supangat, Supangat; Sanad, Zakeya (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
Transparency and accountability based on Sharia provisions are demands in presenting financial reports on Sharia fintech platforms. Based on the principle of taṣarruf al-imām ʿalā al-raʿiyya manūṭ bi al-maṣlaḥa, the Financial Services Authority (OJK) is responsible for ensuring that Sharia fintech financial reports are made by these rules. This article aims to analyze the presentation of financial reports on Sharia fintech platforms, evaluate compliance with OJK provisions, and examine the application of PSAK 101 in reporting practices. PSAK 101, concerning the presentation of Sharia financial reports, has not been adopted by OJK, resulting in inconsistencies in reporting. This study analyzes four Sharia fintech platforms (Alami, Danasyariah, Qazwa, and Ethis) using a normative approach with annual financial report data sources. The results of the analysis show that three platforms have complied with their obligations, but there are variations in the application of PSAK 101. Only Qazwa presents a more comprehensive report. In addition, no platform discloses the temporary partnership fund and social fund required by PSAK 101. This study recommends that OJK reconstruct the law by adopting PSAK 101, preparing detailed temporary partnership funds and social funds guidelines, and strengthening supervision to ensure full accountability in the Sharia fintech sector.